Endings and beginnings : law, medicine, and society in assisted life and death - Palmer, Larry I., 1944- (Praeger, 2000)
As society faces the repercussions of assisted life and death, the news tells of legal battles over frozen embryos and doctors prosecuted after patients' suicide. Palmer argues society should not turn to law and science to determine such intimate matters as how our children are born and how we die.